Understanding the role of policy frameworks in developing land degradation in stakeholders perception from a post‐conflict perspective in Bosnia and Herzegovina. (6th October 2020) - Kapović Solomun, Marijana; Ferreira, Carla S. S.; Barger, Nichole N.; Tošić, Radislav; Eremija, Saša
Abstract: Bosnia and Herzegovina (BiH) is a developing country facing extensive land degradation. BiH exists as a decentralized state, where all land (e.g., agricultural and forest soils) and water resources are under exclusive jurisdiction of two entities and one district, rather than state‐level legislation. Complex land‐related administration occurs between entities that function independently from each other. The lack of coordination among entities frequently leads to political conflicts over land and limited data exchange which may further exacerbate current land degradation. This article investigates (a) stakeholders' perception of land degradation under complex institutional and policy structures; and (b) the current state of land degradation, with a focus on soil erosion as one important indicator of land degradation across the region. As a consequence of the Civil War that took place in BiH between 1992 and 1995, limited data on soil erosion and land status present additional challenges to those seeking to avoid, reduce, and reverse land degradation. Stakeholders reported that the existence of a policy framework as important to addressing land degradation, but not sufficient if implementation is weak. Decision makers reported that the existing policy frameworks are satisfactory, which was in contrast to other stakeholders. Reliable data are crucial for land degradation assessments and development of strategies and policy frameworks, but also better knowledge and awareness of stakeholder perceptions would foster their implementation. In summary, complex institutional structures underpin the weak communication and cooperation among institutions and stakeholders, which presents significant challenges for sustainable land management in post‐conflict societies.